The terrorism reader - Whittaker, David J. (Routledge readers in history, 2007)
Definition of terrorism -- Motivation for terrorism -- Terrorism's wordwide occurrence -- An unholy alliance -- Lebanon I -- Lebanon II -- Libya (terrorists retired) -- Sri Lanka -- Spain -- Northern Ireland -- Algeria -- Peru -- Colombia -- Germany -- Italy -- South africa -- London as target -- Fourteen terrorism case-studies : conclusion -- Terrorism and ethics -- Terrorism and the law -- Counter-terrorism : programmes and strategies